DEVELOPMENT OF A PROBLEM BASED LEARNING E-MODULE TO ENHANCE STUDENTS’ SCIENTIFIC LITERACY IN REACTION RATE LEARNING - Dorthea Maria Woga Nay (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
Students' low scientific literacy in reaction rate learning remains a challenge in chemistry education because existing instructional materials often fail to relate scientific concepts to real-world contexts and provide limited opportunities for active learning. Therefore, innovative teaching materials are needed to promote meaningful, student-centered learning. This study set out to develop a Problem-Based Learning (PBL)-based e-module and and to examine how valid, practical, and effective it is in strengthening students' scientific literacy on the reaction rate topic. The research employed a Research and Development (R&D) approach using the ADDIE model. Validity was established through assessments from both material and media experts, practicality was gauged via student response questionnaires, and effectiveness was tracked through pretest-posttest scientific literacy scores. The material expert validation produced a score of 87.78%, while the media expert validation reached 92.73%, both falling into the very valid category. Student feedback was equally favorable, with practicality percentages of 93.1% in the small-group trial and 92.1% in the large-group trial. In addition, the mean scientific literacy score rose from 53 in the pretest to 87 in the posttest. Taken together, these results indicate that the PBL-based e-module serves as an effective digital resource capable of supporting contextual chemistry instruction and cultivating the scientific literacy skills demanded by twenty-first-century education. ABSTRAK Rendahnya literasi sains peserta didik dalam topik laju reaksi menjadi salah satu tantangan dalam pembelajaran kimia, yang disebabkan oleh keterbatasan bahan ajar yang mampu mengaitkan konsep dengan permasalahan kontekstual serta kurang mendorong partisipasi aktif peserta didik dalam pembelajaran. Oleh karena itu, diperlukan inovasi bahan ajar yang dapat memfasilitasi pembelajaran bermakna melalui pendekatan yang berpusat pada peserta didik. Penelitian ini bertujuan untuk mengembangkan e-modul berbasis Problem Based Learning (PBL) dan menganalisis kevalidan, kepraktisan, dan keefektifannya dalam meningkatkan literasi sains peserta didik pada materi laju reaksi. Penelitian ini menerapkan pendekatan metode Research and Development (R&D) dengan model ADDIE. Kevalidan produk diperoleh dari penilaian oleh ahli materi dan ahli media, kepraktisan diperoleh melalui kuesioner respon peserta didik, sedangkan efektivitas e-modul diperoleh berdasarkan hasil pretest dan posttest literasi sains. Hasil validasi ahli materi terhadap produk menghasilkan skor 87.78%, sedangkan validasi ahli media mencapai 92.73%, yang tergolong dalam kategori sangat valid. Respon peserta didik memperoleh skor 93.1% pada kelompok kecil dan 92.1% pada kelompok besar yang tergolong dalam kategori sangat baik. E-modul juga efektif meningkatkan literasi sains peserta didik dari rata-rata skor 53 menjadi 87. Secara keseluruhan, hasil penelitian ini menunjukkan bahwa e-modul berbasis PBL dapat menjadi alternatif bahan ajar digital yang efektif dan mampu mendukung pengajaran kimia kontekstual serta menumbuhkan keterampilan literasi sains yang dibutuhkan pada pendidikan abad ke-21.